2022
DOI: 10.3390/vaccines10081260
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Psychosocial Factors in Pakistani Parents’ Hesitancy to Vaccinate Their Kids: The Mediating Role of Knowledge and Mistrust of Science about the COVID-19 Vaccine

Abstract: Vaccination is a vital component in the battle against outbreaks of infectious diseases. Recognizing parents’ reluctance to vaccinate their children is even more critical now, given the ongoing threat of a COVID-19 pandemic. Conspiracy theories, vaccination safety concerns, parental efficacy and risk perception, and a lack of confidence in science all influence intention. To investigate how these variables interact with vaccination behavior against COVID-19, we developed a model with psychosocial factors servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…In addition, the literature further confirms the substantial influence of people’s risk perception on the acceptance of vaccination, such as COVID-19 and polio vaccines [ 25 ]. Available evidence shows an inverse relationship between the public perceptions of risk and their actions toward vaccine safety [ 26 ]. Based on past theoretical and empirical works, we conclude that public aversion to vaccination increases as people become aware of and weigh their hazards owing to misinformation, disinformation, and fake news.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the literature further confirms the substantial influence of people’s risk perception on the acceptance of vaccination, such as COVID-19 and polio vaccines [ 25 ]. Available evidence shows an inverse relationship between the public perceptions of risk and their actions toward vaccine safety [ 26 ]. Based on past theoretical and empirical works, we conclude that public aversion to vaccination increases as people become aware of and weigh their hazards owing to misinformation, disinformation, and fake news.…”
Section: Literature Reviewmentioning
confidence: 99%
“…High values of average variance explained (AVE) greater than maximum shared variance values demonstrated discriminant validity for the constructs. The observed AVE values were more than .50, and the square roots of the observed AVEs were larger than the inter factor correlation coefficients, signifying that the constructs satisfied the standard of convergent validity (Shahani et al, 2022). As indicated by Hair et al (2012), we assessed the CRs of constructs and the internal reliabilities of measurement items (α) within the standard cutoff of .70.…”
Section: Descriptive Analysis and Evaluation Of Structural And Measur...mentioning
confidence: 99%
“…Previous studies showed that nearly 20% of parents were hesitated about vaccination, which was related to ignorance about vaccine efficacy [ 5 , 8 , 9 ]. Our findings filled a gap in the study of the effectiveness of vaccines and might enhance the confidence in vaccination in children with hematology and oncology diseases.…”
mentioning
confidence: 99%